Isolation and Characterization of Proteolytic Ruminal Bacteria from Sheep and Goats Fed the Tannin-Containing Shrub Legume Calliandra calothyrsus - McSweeney, Christopher S. (American Society for Microbiology, 1999)
Tannins in forages complex with protein and reduce the availability of nitrogen to ruminants. Ruminal bacteria that ferment protein or peptides in the presence of tannins may benefit digestion of these diets. Bacteria from the rumina of sheep and goats fed Calliandra calothyrsus (3.6% N and 6% condensed tannin) were isolated on proteinaceous agar medium overlaid with either condensed (calliandra tannin) or hydrolyzable (tannic acid) tannin. Fifteen genotypes were identified, based on 16S ribosomal DNA-restriction fragment length polymorphism analysis, and all were proteolytic and fermented peptides to ammonia. Ten of the isolates grew to high optical density (OD) on carbohydrates (glucose, cellobiose, xylose, xylan, starch, and maltose), while the other isolates did not utilize or had low growth on these substrates. In pure culture, representative isolates were unable to ferment protein that was present in calliandra or had been complexed with tannin. One isolate, Lp1284, had high protease activity (80 U), a high specific growth rate (0.28), and a high rate of ammonia production (734 nmol/min/ml/OD unit) on Casamino Acids and Trypticase Peptone. Phylogenetic analysis of the 16S ribosomal DNA sequence showed that Lp1284 was related (97.6%) to Clostridium botulinum NCTC 7273. Purified plant protein and casein also supported growth of Lp1284 and were fermented to ammonia. This is the first report of a proteolytic, ammonia-hyperproducing bacterium from the rumen. In conclusion, a diverse group of proteolytic and peptidolytic bacteria were present in the rumen, but the isolates could not digest protein that was complexed with condensed tannin.